2021
DOI: 10.1124/jpet.121.000667
|View full text |Cite
|
Sign up to set email alerts
|

Kidney-Targeted Delivery of Prolyl Hydroxylase Domain Protein 2 Small Interfering RNA with Nanoparticles Alleviated Renal Ischemia/Reperfusion Injury

Abstract: Background: Inhibition of HIF-prolyl hydroxylase (PHD) has been shown to protect against various kidney diseases. However, there are controversial reports on the effect of PHD inhibition in renoprotection. The present study determined whether delivery of PHD2 siRNA using a siRNA carrier, folic acid (FA)-decorated polyamidoamine dendrimer generation 5 (G5-FA), would mainly target kidneys and protect against renal ischemia/reperfusion injury (I/R). Methods:The renal I/R was generated by clipping the renal pedicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 63 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…Renal function was determined by the levels of plasma creatinine and BUN by using LabAssay Creatinine kit (Fujifilm, Japan) and Vet Axcel Chemistry Analyzer (Alfa Wassermann, NJ) with Urea Nitrogen Reagent Kit, respectively (Xie et al, 2021;Chen et al, 2022a).…”
Section: Renal Function Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Renal function was determined by the levels of plasma creatinine and BUN by using LabAssay Creatinine kit (Fujifilm, Japan) and Vet Axcel Chemistry Analyzer (Alfa Wassermann, NJ) with Urea Nitrogen Reagent Kit, respectively (Xie et al, 2021;Chen et al, 2022a).…”
Section: Renal Function Analysismentioning
confidence: 99%
“…Immunohistochemistry on paraffin-embedded kidney sections was performed as previously reported (Xie et al, 2021;Chen et al, 2022a). In brief, paraffin-embedded sections were deparaffinized and followed by subsequent antigen retrieval, endogenous peroxidase blocking with 3% H 2 O 2 , and nonspecific sites blocking in 10% serum.…”
Section: Immunohistochemical (Ihc) Staining In Kidney Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, systemic HIF activation by VHL loss or xenon-mediated enhanced translation ameliorated AKI [19, 20]. HIF activation limited to the kidney by nanoparticle-based targeted delivery of PHD2 siRNA was sufficient to protect against IRI [21]. Accordingly, VHL deletion restricted to the thick ascending limb conveyed substantial protection against ischemic kidney injury elucidating the importance of this nephron segment [22].…”
Section: Hif Activation Protects Against Acute Kidney Injurymentioning
confidence: 99%
“…Drug nanoformulation is a viable option for improving the on-target tissue accumulation of drugs [ 37 , 38 ]. Recently, a relevant study demonstrated that, in a mouse model of acute kidney injury, the intravenous injection of polyamidoamine dendrimer-wrapped PHD2 siRNA nanoparticles with folate decoration results in nanoparticle accumulation most in the kidneys and significantly reduces reperfusion injury [ 39 ]. To date, however, the nanoformulation of PHD inhibitors remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%